Implementación de un sistema didáctico de tres ejes para la clasificación de objetos por forma utilizando visión artificial para el laboratorio de Electromecánica de la UTC Extensión La Maná. - Catota Chango, Wilmer Wladimir (2023)
One of the very interesting lines of research and development is related to the "imitation" of our sense organs: hearing and vision. In this, it is expected not only to provide a computer with the capacity to "perceive" sounds, but also to recognize, that is, to "identify" what is perceived. Significant progress has been made in speech recognition, while less progress has been made in terms of vision-interpretation. Computer vision is a growing discipline with a multitude of applications, such as automatic inspection, object recognition, detection, robotics, etc. The future is even brighter; the creation of autonomous machines capable of intelligently interacting with the environment requires, however, the ability to perceive it. These machines, equipped with increasingly fast and powerful computers, find one of their greatest limitations in the processing and interpretation of the information provided by visual sensors. The purpose of this project is to contribute scientific, educational knowledge and technological advances to the electromechanical engineering career of the Technical University of Cotopaxi through the implementation of an object classification equipment using artificial vision that will later be destined for the laboratory of the same race.